Em busca do convencimento : disputas político-eleitorais entre pessedistas e petebistas no Rio Grande do Sul (1945-1954) - Asturian, Marcos Jovino (2011)
This study seeks to understand the electoral dispute between the Partido Social Democrático (PSD) and the Partido Trabalhista Brasileiro (PTB) in the elections of 1947, 1950 and 1954 for governor of Rio Grande do Sul through the pages of the newspaper Diário de Noticias, setting up a study political history of documentary sources as having the press. For this purpose, we use the analytic tradition on theconcept of ideology, updated John Thompson, as a general interpretation of a possible historic role of symbolic forms in the universe of political. The central role of mass media, particularly the written press, is the common point of conceptual reflection on the history and sociology of the media. Both the PSD and the PTB using the newspaper as a mechanism of production and propagation of possessing depictions of political content. Therefore we are interested in how the symbolic forms were created, in particular circumstances, serving to establish and sustain relations of domination